A critical realist exploration of the implementation of a new curriculum in Swaziland - Pereira, Liphie (Rhodes University, Faculty of Education, Department of Education, 2012)
This study offers an in-depth exploration of the conditions from which the implementation of a curriculum called the International General Certificate of Secondary Education (IGCSE), later localised into Swaziland General Certificate of Secondary Education (SGCSE), emerged and the constraining and enabling conditions for the implementation of the new I/SGCSE curriculum. It derives its theoretical foundation from Roy Bhaskar's critical realism and Margaret Archer's concept of analytical separability. The study therefore offers explanations about the curriculum change and its implementation that are based on how structural, cultural, and agential mechanisms operating at a deeper level of reality (the intransitive layer of reality or the domain of the real) and existing independently of what we see, know or believe of them (the transitive layer of reality or domains of the actual and empirical) interacted to condition the emergence of I/SGCSE and the way it is implemented. I conduct a critical discourse analysis of relevant literature, I/SGCSE documents and interview data in order to identify those mechanisms that were cultural and also those that were structural and agential. Bernstein's concepts of classification and framing are used to analyse observation data in order to explore the influence of these mechanisms on the teaching practices of the teachers who took part in the study. Analysis of the data suggests that the change from General Certificate of Education Ordinary Level (GCE O-level) to I/SGCSE was conditioned by inconsistencies between the cultural and structural mechanisms of the Swazi context. Many of the cultural elements of the Swazi context such as the discourses of good citizens, of competitive advantage, and of quality education draw from global discourses which view relations between people from a postmodernist position and therefore support weakly classified and framed pedagogic practices. In contrast, the discourse of morality and many of the structural elements of the Swazi context, such as the pre2006 education system and the Tinkhundla government system, all view reality from a modernist position, therefore supporting strong relations of power and control. The cultural system therefore exerted more influence in conditioning the change from the strongly classified and framed GCE O-level curriculum to the weakly classified and framed I/SGCSE curriculum. Furthermore, the analysis of interview and observation data suggests that inconsistencies between the global discourses and the discourses and structures that teachers confront in their day-to-day lives, together with the decisions teachers made in response to structural constraints, created constraining conditions for the change from GCE O-level to I/SGCSE. The study adds to knowledge on curriculum change and implementation through insights into the enabling and constraining effects of mechanisms operating at a deeper level of reality on curriculum-change decisions and on the ability of teachers to implement curriculum changes. The focus on the deeper level of reality may therefore contribute towards emancipatory knowledge which could be used not only by the Ministry of Education and Training and teachers in Swaziland but also elsewhere to inform future planning, decision making, and practice in relation to curriculum change and implementation.
Keywords: Critical realism; Education -- Philosophy; Critical pedagogy -- Swaziland; Curriculum change -- Swaziland; Education -- Swaziland; Education and state -- Swaziland; Education -- Aims and objectives -- Swaziland; Critical discourse analysis; International General Certificate of Secondary Education